ERROR ANALYSIS IN ORAL PRODUCTION MADE BY STUDENTS OF CIVIL ENGINEERING A CASE STUDY IN ENGLISH TUTORIAL PROGRAM (ETP) AT UNIVERSITAS MUHAMMADIYAH SURAKARTA - Firdausi, Aulia Putri (JoLLIET, 2016)
This research paper is aimed to classify the type of errors, analyze thefrequency and dominant, and explain the sources of error. The type of thisresearch is descriptive research. The research collects English TutorialProgram record as the source of the data. The research uses documentationmethod to select the data. There are 305 data containing of errors. Theresearcher use Clark and Clark theory and Dulay Burt, and Krashen theory toanalyze the error. They are speech error, morphological error and syntacticalerror. In speech errors are filled pause (81, 96%), Repeat (44, 27%), SilentPause (19, 67%), Stutters (6, 22%), Injection (1, 96%), correction (0, 65%),Slip of the Tongue (0, 98%). Morphological error are vocabulary error (1,96%), Pronunciation (9, 83%), Omission of Bound (1, 63%). Syntactical errorare omission of Modal (will) (1, 31%), omission of preposition (1, 31%),Question Construction (1, 31%) and the last Wrong in Word Selection (0,65%).Key Words: error analysis, oral production